Perkawinan Anak dalam Perspektif Hukum Keluarga Islam dan Hukum Positif di Indonesia: Studi Kasus Aceh - Asniah Asniah; Sri Andayani binti Mahdi Yusuf (Journal of Innovative and Creativity, 2025)
Child marriage is a socio-legal phenomenon that is still prevalent in Indonesia, particularly in Aceh, despite national regulations setting a minimum age for marriage. This article aims to analyze child marriage from the perspective of Islamic family law and positive law, as well as to examine how this practice occurs in Aceh, which has specific characteristics in the application of Islamic law. This study uses a normative legal method with a legislative, conceptual, and socio-legal approach, accompanied by a review of literature and empirical data from court reports. The results of the study show that classical Islamic law does not explicitly set a minimum age for marriage, but through the maqashid al-syari'ah approach, it can be understood that preventing child marriage is part of efforts to preserve offspring (hifz al-nasl) and protect children. On the other hand, Indonesian positive law through Law No. 16 of 2019 sets a minimum age of 19 for both men and women, but its implementation in Aceh faces challenges in the form of local culture, customary authority, and low legal literacy among the community. The widespread practice of marriage dispensations in the Aceh Religious Court shows a gap between formal regulations and the living law embraced by the community. This article emphasizes that the harmonization of Islamic law, positive law, and customary law in Aceh must be carried out through a comprehensive approach involving religious scholars, the government, educational institutions, and civil society. Preventing child marriage is not only a legal requirement but also part of the Sharia's mission to protect the younger generation as the nation's asset.